Security and Privacy Challenges in the Internet of Things - Mayer, Christoph (Electronic Communications of the EASST, 2009)
The future Internet of Things as an intelligent collaboration of miniaturized sensors poses new challenges to security and end-user privacy. The ITU has identified that the protection of data and privacy of users is one of the key challenges in the Internet of Things [Int05]: lack of confidence about privacy will result in decreased adoption among users and therefore is one of the driving factors in the success of the Internet of Things. This paper gives an overview, categorization, and analysis of security and privacy challenges in the Internet of Things.